2020
DOI: 10.17821/srels/2020/v57i5/155250
|View full text |Cite
|
Sign up to set email alerts
|

Usability Analysis of Library Websites of National Institutes of Technology of India: An Evaluation

Abstract: To maintain the standard, design and structure of Indian academic library websites, regular assessment of library web portals to increase their usability and accessibility is necessary. The purpose of this study is to evaluate the usability, efficiency, and effectiveness of thirty National Institutes of Technology (NIT) Libraries websites in India. Most of the selected Libraries websites are very simple and had very basic and common usability features in terms of General Information, Available library services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
1
Order By: Relevance
“…Data yang terkumpul dalam bentuk kata-kata atau lisan dideskripsikan dalam tulisan. Penelitian kualitatif deskriptif digunakan untuk meneliti dan memahami kondisi objek secara alamiah [18]. Data kualitatif diperoleh melalui observasi dan wawancara mendalam dengan responden, yang dalam hal ini adalah pustakawan di Dinas Arsip dan Perpustakaan Kota Bandung.…”
Section: Metode Penelitianunclassified
“…Data yang terkumpul dalam bentuk kata-kata atau lisan dideskripsikan dalam tulisan. Penelitian kualitatif deskriptif digunakan untuk meneliti dan memahami kondisi objek secara alamiah [18]. Data kualitatif diperoleh melalui observasi dan wawancara mendalam dengan responden, yang dalam hal ini adalah pustakawan di Dinas Arsip dan Perpustakaan Kota Bandung.…”
Section: Metode Penelitianunclassified
“…In another study, Verma & Shukla (2018) "evaluated the efficiency, usability, and effectiveness of 14 Indian Institute of Management library websites and found that most of the IIMs' library websites have simple and common usability features. All the libraries under study have a separate webpage and 29% libraries have multilingual options.…”
Section: Literature Reviewmentioning
confidence: 99%